IOT Based Smart Lamp for Efficient Usage of Electrical Energy - Herpendi Herpendi; Veri Julianto; Khairul Anwar Hafizd; Rabini Sayyidati (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
The government is proclaiming the electrical energy saving campaign in order to raise the people’s awareness of its importance. The Ministry of Energy and Mineral Resources (ESDM Ministry) of the Republic of Indonesia stated that a year of energy saving equals to the amount of saving Rp43.000.000.000.000,00 (forty three trillion rupiah) of money, which is also equal to a construction of electric steam power plant with the capacity of 3.500 megawatts (MW). One of the programs that has been encouraged by the government is the 'turn off the light' campaign. Turning off lights is a simple but often neglected thing. Apart from the limited awareness to save the energy for a better future, people are often too busy to do it. In 2015, Taruna built an Arduino Micro-controller based light control system using Android smartphone to provide ease, specifically for physically disabled and elderly. The shortcomings of this system are that the lights cannot be turned on and off automatically (smart) with timer and it can only be controlled at close range (bluetooth). Development of technology with the internet guide can easily help human, and thus, this research aims to improve the system with the time control (timer) and close range control (bluetooth) as well as the long range using SMS and internet. The system is built with the prototype model that incude the communication, fast planning, fast prototype designing and building, system submission and feedback. The result of this system building is that the light can be controlled using bluetooth and also provide a faster response time; less than a second (as well as the timer). The light can also be controlled from a long range using the internet connection, giving a response time between 14 to 17 seconds. When a light control command occurs, the SMS notification is sent to the cell phone of the user. Using this system, the light can be controlled correctly in order to conveniently give the user effectivity and efficiency in electrical energy usage.